Effect of fuel jet arrangement on the mixing rate inside trapezoidal cavity flame holder at supersonic flow. (13th August 2019) - Du, Sunwen; Al-Rashed, Abdullah A.A.A.; Barzegar Gerdroodbary, M.; Moradi, Rasoul; Shahsavar, Amin; Talebizadehsardari, Pouyan
Abstract: Fuel mixing inside the supersonic combustion chamber is a significant process for development of modern scramjets. In this article, computational fluid dynamic (CFD) approach is applied to investigate the effect of various fuel injections on the mixing rate inside the supersonic combustion chamber. The mixing of hydrogen jets with four different arrangements inside the cavity flame holder is comprehensively studied. In order to examine the effect of multi jets within a cavity flameholder, a three-dimensional model is established and Navier-stocks equations are solved to simulate the flow and mixing zone inside a cavity region. Obtained results show that the injection of hydrogen jet from the bottom of cavity flame holder considerable enhances the ignition zone within the cavity. Moreover, the backward fuel injection is more superior to forward fuel injection since low-pressure vortex could significantly distribute the fuel and enlarge the mixing zone inside the cavity flame holder. Highlights: 3D simulations were performed to study the multi hydrogen jets within cavity. Mass distribution and stream line of fuel are comprehensively investigated. Arrangement of multi fuel jets on mixing rate of H2 gas inside the cavity is studied. The injection of fuel from the back wall step is more efficient than other position.